Current status of therapy for chronic myeloid leukemia: a review of drug development. (June 2008) - Padmanabhan, Swami; Ravella, Saritha; Curiel, Tyler; Giles, Francis
Chronic myeloid leukemia (CML) has led the way for developing rational drug development in cancer. Most cases of CML diagnosed and treated in chronic phase are extremely well controlled with imatinib monotherapy, and primary resistance is very uncommon. Even though the treatment failure rate is low, the emergence of drug resistance and the lack of eradication of the hematopoietic stem cell clone has prompted a wave of drugs to address one or both these problems. Several clinical trials (Phase I and II) of dasatinib or nilotinib in the treatment of imatinib-resistant or -intolerant Ph chromosome-positive leukemia have already reported a remarkable rate of hematologic response greater than 90% for chronic-phase patients. These drugs minimize the risk of acquired drug resistance that is particularly seen within the first 24––36 months of therapy, and can prevent early failure in these patients, Furthermore, rational, noncross-resistant combinations that include a T315I inhibitor and drugs that can eradicate the hematopoietic stem cell clone may extend the coverage to virtually all patients with bcr-abl. Here we review the 6-year impact of the ''magic pill'', Gleevec ®®, (Glivec ®® ), including the emerging problems with its treatment, the efficacy data of dasatinib and nilotinib and the very promising data of the newer generation of drugs for CML.